Pengembangan Sistem Anti Plagiasi Praktikum di Lingkungan Laboratorium Pembelajaran Fakultas Ilmu Komputer Universitas Brawijaya - Rizki Maulana Akbar; Bayu Priyambadha; Eriq Muhammad Adams Jonemaro (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Practicum is a structured academic activity conducted in a particular laboratory or class with the aim of providing technical experience to practicum participants. But there are some obstacles in practicum. One of the main obstacles to be highlighted is high level of plagiarism that have potential to occur in practicum activities. That high level of plagiarism is also supported by assistant's condition who also being a student which have limited time for checking plagiarism and assessment of source code which must be compile and run. So it's almost impossible to identify plagiarism accurately. Therefore, it is necessary to have a system that help assistant in identifying plagiarism and correcting the practicum assignment. System must be able to detect plagiarism potential by applying levenshtein distance algorithm for document checking and plagiarism potential inspection in program code with abstract syntax tree. In addition, the system must also be able to run the program code directly with the cloud compiler on the system interface without having to download and run every source code. System developed using the Spring and Vue framework and built for improving the productivity of assistants in correcting and plagiarism identification and also expected to decrease the level of plagiarism in practicum activities. System is tested by whitebox testing specifically unit testing and integration using JUnit and Mockito, also tested valid by validation testing for 32 functional requirements and 1 non-functional requirement.